Feminisms a global history - Delap, Lucy 1972- (The University of Chicago Press, 2020)
Frontmatter -- Contents -- List of Illustrations -- List of Abbreviations -- Introduction -- CHAPTER 1 Dreams -- CHAPTER 2 Ideas -- CHAPTER 3 Spaces -- CHAPTER 4 Objects -- CHAPTER 5 Looks -- CHAPTER 6 Feelings -- CHAPTER 7 Actions -- CHAPTER 8 Songs -- CONCLUSION Global Feminisms -- Acknowledgements -- Notes -- Further Reading -- Index